Competency Training for Building Modeling and Information Design Department at SMK LEMURIA Kudus - Yayan Adi Saputro; Khotibul Umam; Nor Hidayati; Decky Rochmanto; Ariyanto; Ahmat Wakit (PT FORMOSA CENDEKIA GLOBAL, 2023)
LEMURIA Kudus Vocational School is a vocational high school that has the potential to be developed because it is aligned with the field of science, namely civil engineering or more specifically related to building construction. So far, students of Building Information and Modeling Design have only studied images, with a coaching program that leads them to be able to apply them in the world of work. The guidance referred to in this proposed program is